Role of courts in enforcing competition laws: a comparative analysis of India and Pakistan. (25th September 2018) - Darr, Amber
Abstract: Developing countries adopt modern competition laws based on international blueprints for motivations ranging from gaining international legitimacy to achieving domestic economic goals. However, whilst adopting such laws confers some legitimacy on the competition regimes of these countries, it does not automatically translate into the realization of their economic goals unless the laws are also meaningfully enforced. Comparative law literature, viewed in the light of development economics, suggests that meaningful enforcement entails, among other things, a productive interaction between the adopted laws and the pre-existing legal systems of the countries. In this article, I identify possible interactions between competition laws and pre-existing legal systems in India and Pakistan and compare the interactions that actually occur in the two countries. I observe that, although India and Pakistan have nearly identical pre-existing legal systems and adopted similar competition laws within five years of each other, the interactions of these competition laws with the pre-existing legal systems in the countries are remarkably different. I argue that the nature of interactions in a country is substantially shaped by the strategy, mechanisms, and legal and political institutions through which it adopts its competition law. I also demonstrate that the type of interaction has an observable impact on the enforcement of competition law in that country.